The phantom tollbooth - Juster, Norton; Feiffer, Jules (HarperCollins Children's London, 2008)
Milo is bored. But all that changes when he receives a mysterious Tollbooth through the post. Having nothing better to do, Milo points his little car towards the strange land beyond the Tollbooth. And before he knows what he's doing, he's entered the Kingdom of Wisdom, where everything is unexpected